STRATEGI DINAS KETAHANAN PANGAN DAN PERTANIAN DALAM MENGELOLA STOK BERAS DI MEDAN - Rachmawati, Yeni; Husna, Asmaul; Surbakti, Eka Wulandari; Sibuea, Buhari; Aulia, Vityaloka (Smart Education, 2025)
Abstract: Rice stock management is very important in maintaining food security. This article aims to formulate an optimal strategy for rice stock management carried out by the Food Security, Agriculture and Fisheries Agency in Medan City by integrating SWOT analysis through the IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) matrices. The study combines field research findings with relevant theories and references on rice stock management and food security in urban areas. The strategies derived from the SWOT analysis using the IFAS and EFAS matrices include strengthening the digital monitoring system, developing urban farming, fostering cross-sectoral collaboration, and improving evidence-based policies. Keywords: rice; EFAS; IFAS; strategy; SWOT. Abstrak: Pengelolaan stok beras merupakan hal yang sangat penting dalam menjaga keamanan pangan. Artikel ini bertujuan merumuskan strategi optimal pengelolaan stok beras yang dilakukan Dinas Ketahanan Pangan, Pertanian dan Perikanan di Kota Medan dengan mengintegrasikan analisis SWOT melalui matriks IFAS (Internal Factor Analysis Summary) dan EFAS (External Factor Analysis Summary). Kajian mengkombinasikan hasil penelitian lapangan dengan teori dan referensi yang relevan mengenai pengelolaan stok beras dan ketahanan pangan di daerah perkotaan. Strategi yang dihasilkan dari analisis SWOT dengan menggunakan matriks IFAS dan EFAS adalag memperkuat sistem monitoring digital, pengembangan urban farming, kolaborasi lintas sektor, dan perbaikan kebijakan berbasis bukti. Kata kunci: beras; EFAS; IFAS; strategi; SWOT.